Hodnocení výkonnosti společnosti s využitím Balanced Scorecard - Somrová, Adéla (Vysoké učení technické v Brně. Fakulta podnikatelská, 2024)
Diplomová práce je zaměřena na hodnocení výkonnosti společnosti SAKO Brno, a.s. pomocí modelu Balanced Scorecard. Teoretická východiska přibližují potřebná témata v oblasti výkonnosti podniku včetně přístupů k měření výkonnosti. Analytická část práce zahrnuje představení analyzovaného podniku a analýzu současného stavu společnosti SAKO Brno, a.s. pomocí vybraných analýz. Poslední část se zabývá, na základě zjištěných informací z analytické části, navržením implementace modelu BSC do společnosti spolu s přínosy a analýzou možných rizik.

The diploma thesis focuses on assessing the performance of the company SAKO Brno, a.s. using the Balanced Scorecard model. The theoretical background introduces necessary topics in the field of business performance, including approaches to performance measurement. The analytical part of the thesis includes the presentation of the analyzed company and the analysis of the current state of SAKO Brno, a.s. through selected analyses. The final part, based on the findings from the analytical section, deals with proposing the implementation of the BSC model into the company, along with the benefits and analysis of possible risks.
The Performance Evaluation of the Company using Balanced Scorecard
Keywords: Balanced Scorecard; perspektivy BSC; hodnocení výkonnosti; finanční analýza; strategická analýza; strategická měřítka; strategické cíle; analýza rizik; Balanced Scorecard; BSC perspectives; performance evaluation; financial analysis; strategic analysis; performance measures; strategic objectives; risk analysis